2 2 0 2 + 2 2 1 2 + 2 2 2 2 + 2 2 3 2 + ⋯
If the value of above expression is in the form A , find the value of A .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let y be the nested radical, then we have:
y ⇒ y ⇒ x x 2 x 2 − x − 2 ( x − 2 ) ( x + 1 ) ⇒ x ⇒ y ⇒ A = 2 2 0 2 + 2 2 1 2 + 2 2 2 2 + 2 2 3 2 + . . . = 2 2 + 2 2 2 + 2 4 2 + 2 8 2 + . . . = 2 1 2 + 2 + 2 + 2 + . . . Let x = 2 + 2 + 2 + 2 + . . . = 2 x = 2 + x = 2 + x = 0 = 0 = 2 x > 0 = 2 x = 2 2 = 2 = 2
Thanks, you clear my doubt
We can solve this by approximation method also. If we see the first term 2/2^2^0=1 and the remaining all term cannot be greater than 1 . ao, it means the total value cannot be greater than 2. So, The answer is 2.
Problem Loading...
Note Loading...
Set Loading...
We multiply S by 2 1 and try to push it inside the nested radicals:
2 S = 2 1 × 2 2 0 2 + 2 2 1 2 + …
⇒ 2 S = 2 1 × ( 2 2 0 2 + 2 2 1 2 + … )
⇒ 2 S = 2 2 1 2 + 2 1 × ( 2 2 1 2 + … )
⇒ 2 S = 2 2 1 2 + 2 2 2 2 + 2 2 1 × ( … )
We realise that this sequence is the same as S 2 without it's first term, so:
⇒ 2 S = S 2 − 2 2 0 2
⇒ 2 S 2 − S − 2 = 0
Solving the quadratic, we get S = 2 , − 2 1 .
But, since S is positive, ( S = − 2 1 ) is discarded. Hence:
⇒ S = A = 2
⇒ A = 2